Modification of the PthA4 effector binding elements in Type I CsLOB1 promoter using Cas9/sgRNA to produce transgenic Duncan grapefruit alleviating XccΔpthA4:dCsLOB1.3 infection. Issue 5 (2nd November 2015) - Jia, Hongge; Orbovic, Vladimir; Jones, Jeffrey B.; Wang, Nian
Summary: Citrus canker caused by Xanthomonas citri subspecies citri (Xcc) is a severe disease for most commercial citrus cultivars and responsible for significant economic losses worldwide. Generating canker‐resistant citrus varieties will provide an efficient and sustainable solution to control citrus canker. Here, we report our progress in generating canker‐resistant grapefruit by modifying the PthA4 effector binding elements (EBEs) in the CsLOB1 Promoter (EBEPthA4 ‐CsLOBP) of the CsLOB1 ( Citrus sinensis Lateral Organ Boundaries) gene. CsLOB1 is a susceptibility gene for citrus canker and is induced by the pathogenicity factor PthA4, which binds to the EBEPthA4 ‐CsLOBP to induce CsLOB1 gene expression. There are two alleles, Type I and Type II, of CsLOB1 in Duncan grapefruit. Here, a binary vector was designed to disrupt the PthA4 EBEs in Type I CsLOB1 Promoter (TI CsLOBP) via epicotyl transformation of Duncan grapefruit. Four transgenic Duncan plants with targeted modification of EBEPthA4 ‐T1 CsLOBP were successfully created. As for Type I CsLOB1 promoter, the mutation rate was 15.63% (#D13), 14.29% (#D17), 54.54% (#D18) and 81.25% (#D22). In the presence of wild‐type Xcc, transgenic Duncan grapefruit developed canker symptoms similarly as wild type. An artificially designed dTALE dCsLOB1.3, which specifically recognizes Type I CsLOBP, but not the mutated Type I CsLOBP or Type II CsLOBP, was developed to infect Duncan transformants. Consequently, #D18 had weakened canker symptoms and #D22 had no visible canker symptoms in the presence of XccΔpthA4:dCsLOB1.3. Our data suggest that activation of a single allele of susceptibility gene CsLOB1 by PthA4 is sufficient to induce citrus canker disease, and mutation in the promoters of both alleles of CsLOB1 is probably required to generate citrus canker‐resistant plants. This work lays the groundwork to generate canker‐resistant citrus varieties via Cas9/sgRNA in the future.